DIAGNOSTICS OF THE HIGH-TORQUE ELECTRICAL MOTOR UNDER OPERATING CONDITIONS AT LOW TEMPERATURES IN VACUUM - A. V. Byeli; A. N. Karpovich; E. G. Bilenko (Приборы и методы измерений)
Parameters of high-moment electrical motor working at low-temperatures and high vacuum were investigated. It has been demonstrated that pressure in conspiracy with temperature does not influence starting current of the motor. Temperature reduction from 293 up to 143 K increases starting current at a factor of 3.5.